Electronic properties of tetraazaperopyrene derivatives on Au(111): energy-level alignment and interfacial band formation - Stein, Arnulf; Rolf, Daniela; Lotze, Christian; Feldmann, Sascha; Gerbert, David; Günther, Benjamin; Jeindl, Andreas; Cartus, Johannes J.; Hofmann, Oliver; Gade, Lutz H.; Franke, Katharina J.; Tegeder, Petra (The journal of physical chemistry. C, Energy, materials, and catalysis, 2021)
N-heteropolycyclic aromatic compounds are promising organic electron-transporting semiconductors for applications in field-effect transistors. Here, we investigated the electronic properties of 1,3,8,10-tetraazaperopyrene derivatives adsorbed on Au(111) using a complementary experimental approach, namely, scanning tunneling spectroscopy and two-photon photoemission combined with state-of-the-art density functional theory. We find signatures of weak physisorption of the molecular layers, such as the absence of charge transfer, a nearly unperturbed surface state, and an intact herringbone reconstruction underneath the molecular layer. Interestingly, molecular states in the energy region of the sp- and d-bands of the Au(111) substrate exhibit hole-like dispersive character. We ascribe this band character to hybridization with the delocalized states of the substrate. We suggest that such bands, which leave the molecular frontier orbitals largely unperturbed, are a promising lead for the design of organic-metal interfaces with a low charge injection barrier.
Gesehen am 04.11.2021